ONLINE TEACHING OF ENGLISH FOR LIBRARIANS: STUDENTS’ PERCEPTION OF THE USE OF VOICE NOTE AND ITS CONTRIBUTION TO THEIR ENGLISH SPEAKING - dalilan, Dalilan; Nuraini (JAMI: Jurnal Ahli Muda Indonesia, 2022)
Objective. This study deals with the use of online teaching of English for librarians using WhatsApp voice notes. This study aimed at figuring out the students’ perspectives regarding the implementation of WhatsApp voice notes in teaching English for Librarian courses and investigating to what extent WhatsApp voice is contributing to their speaking skills. Material and Method. Four examples of dialogue in a library context were used in practice involving 68 students taking English as a Librarian subject. The instrument used to collect data for the study was a questionnaire survey and coding and summarizing were used to analyze the data. Results. The result of the study showed that the highest percentage (84%) of the participants perceived speaking interchange via voice note as a more helpful way of making and reinforcing their speaking fluency. Independent practice and replayed recordings make their speaking fluency reinforced. The result also showed that the voice notes recordings of their speaking become valuable self-assets for their speaking practice in the library context (76%) and help them recognize new vocabulary and pronunciation in library science (67%). Conclusion. Based on the findings, it can be concluded that WhatsApp voice note is a useful tool to provide students with opportunities to speak using voice note as an alternative media, to trigger and train student’ self-speaking skill.